Technology and the Effect of Multimedia Usage in the 2023 Election in Nigeria - Inobemhe, Kelvin; Ja'afaru, Sharifatu; Garba, Suleiman (Asian Journal of Media and Communication, 2024)
This paper delves into the multifaceted effect of multimedia usage in Nigerian elections, exploring its role, challenges, and implications for democratic governance. This study relied on media effects theories, such as agenda setting, framing theory, and social influence theory, to analyse the impact of multimedia on voter perceptions, attitudes, and behaviour, as well as its role in shaping campaign strategies and fostering political engagement. Drawing upon a range of scholarly literature and empirical evidence, this study elucidated how multimedia, encompassing various platforms such as television, radio, newspapers, social media, and online platforms, has become integral parts to the electoral landscape in Nigeria. However, alongside its benefits, the proliferation of misinformation and fake news emerged as a significant challenge during elections, exacerbated by the decentralised nature of social media and the digital divide. Political polarisations, social divisions, and the manipulation of social media further complicated the electoral landscape, hindering constructive dialogue and undermining electoral integrity. Regulatory frameworks governing multimedia usage in elections were fragmented and inconsistent, necessitating comprehensive reforms to enhance transparency, accountability, and ethical standards. Addressing these challenges requires a multi-stakeholder approach involving government agencies, civil society organisations, media practitioners, and technology companies. By bridging the digital divide, promoting media literacy, and fostering ethical standards, Nigeria can strengthen its democratic foundations and promote inclusive and transparent electoral processes.